Epitope Identification in BEFV Gene for Detecting Effective Points - Shima Molazadeh; Hadi Keivanfar; Mehran Bakhshesh; Gholamreza Nikbakht Brujeni (Fasa University of Medical Sciences, 2022)
Background & Objective: The most common cause of milk production loss in cattle and water buffalo is bovine ephemeral fever (BEF). Previous cases have been reported in Iran's south regions, with a low mortality rate. As a result, studying BEFV and identifying ideal epitopes for further developing diagnostic paths is important. Materials & Methods: To investigate BEFV N protein epitopes, we collected samples, extracted and sequenced DNA, and then used the ExPaSy translate method to deduce the amino acid sequence. Various immunoinformatics techniques were used to analyze physical/chemical properties, secondary structure of protein sequences, membrane topology, antigenic property, and 3D structure. BCPRED and the DiscoTope server, respectively, predicted linear and discontinuous epitopes of BEFV N protein. Finally, the PatchDock server was used to dock peptides and antibodies. Result: Three linear epitopes and sixteen discontinuous epitopic positions were discovered. Furthermore, molecular docking between epitopes and low-binding-energy antibodies revealed that they have easy access to the immune system. Conclusion: In this study, bioinformatics techniques were used to predict epitopes of the BEFV N protein for further developing BEFV diagnostic paths. Furthermore, experimental validation is needed for these epitopes.